Business Process Reengineering melalui Implementasi Artificial Intelligence pada UMKM di Kabupaten Ciamis - Luffi Septian; Rian Dwicahya S.; Maulana Sidiq; Nana Yudi Permana; Dadan Mulyana (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2026)
Micro, small, and medium enterprises (MSMEs) often adopt digital tools by automating isolated tasks while inefficient end-to-end workflows remain unchanged. This article develops a contextual Business Process Reengineering (BPR) framework for integrating Artificial Intelligence (AI) into MSMEs in Ciamis Regency. The study applies an integrative literature review that combines peer-reviewed studies published mainly in 2021–2026, foundational BPR literature, official statistics, and Indonesian AI governance documents. The synthesis identifies six priority process domains: marketing and content, customer service, sales and order management, inventory and procurement, finance and administration, and quality and organizational knowledge. The proposed framework comprises five phases: diagnosing the AS-IS process, prioritizing high-value processes, designing the TO-BE process with suitable AI, piloting and integrating the solution, and governing, measuring, and scaling the redesigned process. Data readiness, human-in-the-loop controls, cybersecurity, ethics, and measurable key performance indicators are treated as cross-cutting requirements. The findings indicate that generative AI, forecasting, document intelligence, and conversational systems can improve process performance when embedded in redesigned workflows rather than added to existing routines. The framework offers a practical roadmap for MSMEs, local government, technology providers, and universities, while requiring field validation before causal performance claims can be made.